Pertumbuhan Daun Angsana (Pterocarpus indicus Willd) dan Akumulasi Logam Timbal (Pb) - Gita Prima Yudha; Zozy Aneloi Noli; M. Idris (Jurnal Biologi Universitas Andalas, 2013)
An examination of lead accumulation on leaves growth Angsana (Pterocarpus indicus Willd) was conducted from August to November 2012 in Plant Physiology Laboratory, Andalas University, Padang. The aim of the study was to find correlation between accumulation of lead and leaves size and stomatal density. Statistical analysis used kruskal wallis-test and linear regression. The result showed that Angsana’s leaves stopped growing after 25 days old with achieved 25.99 cm width, 345 per mm2 stomatal density and 0.73 mg per gr of chlorophyll content. Concentration of lead increased gradually from 0.00 mg per kg at early and 0.021 mg per kg in 25 days. There was no significant correlation between age of leaves and lead concentration. However, there was a positive correlation between width of leaves and lead concetration (R= 0.862).Keywords: Pterocarpus indicus, accumulation of Pb, age and size of leave.